Child and Adolescent Social Adaptive Functioning Scale: Factorial Invariance, Latent Mean Differences, and Its Impact on School Refusal Behavior in Spanish Children - Gonzálvez, Carolina; Inglés, Cándido J.; Martínez-Palau, Ainhoa; Sanmartín, Ricardo; Vicent, María; García-Fernández, José M. (Frontiers in Psychology, 2019)
This study aims to examine the factorial invariance and latent mean differences across gender of the Spanish version of the Child and Adolescent Social Adaptive Functioning Scale (Study 1) and to value the function of social functioning as a protective ability of school refusal behavior (Study 2). Participants were Spanish students aged 8–12 years carefully chosen by simple random cluster, 345 for the first study (M = 9.17; SD = 1.03) and 1,032 students for the second study (M = 10.02; SD = 1.77). The measures used were the Child and Adolescent Social Adaptive Functioning Scale (CASAFS) and the School Refusal Assessment Scale-Revised (SRAS-R). Results about the validation of the scale supported the model proposed in this study for the CASAFS, with 15 items and a four-factor structure (school performance, peer relationships, family relationships, and home duties/self-care). Findings revealed invariance across gender for this model and good internal consistency levels were exhibited in each of the four dimensions of the CASAFS (0.76, 0.72, 0.74, and 0.71). Latent mean differences did not report differences between boys and girls. Regarding the second study, the social functioning acted as a protective factor of school refusal behavior by negatively and significantly predicting high scores in school refusal behavior due to anxiety symptoms or feelings of negative affect linked to the obligation to attend school. Opposite results were found for those students who justify their refusal to attend school in pursuing tangible reinforcements outside the school setting. These findings strengthen the reliability and validity of the CASAFS and the idea of social functioning as a person’s ability which could prevent school refusal behavior is discussed.